Novel approaches to the assessment of cardiorespiratory readiness of patients after coronary artery bypass surgery aimed to the efficient cardiac rehabilitation performance - Tea T. Kakuchaya (Concilium Medicum, 2021)
Aim. To develop novel strategies of patients selection and risk stratification after coronary artery bypass surgery before starting aerobic cardiorespiratory training programs.